3D numerical simulation of a rotating packed bed with structured stainless steel wire mesh packing. (12th October 2017) - Liu, Yi; Luo, Yong; Chu, Guang-Wen; Luo, Jiang-Zhou; Arowo, Moses; Chen, Jian-Feng
Graphical abstract: The 3D packing's model, which has same structure and size as the physical packing, was employed for the CFD simulation of the gas pressure drop and gas flow in a RPB. Highlights: A 3D physical model of rotating packed bed with structured packing was built. CFD simulation results of gas pressure drop agreed well with experimental data. Gas pressure drop of the inner cavity zone is the major contributor to overall gas pressure drop. Detailed gas flow inside the RPB was obtained by the simulation results. Gas-side end effect at the outer annular packing zone was proposed. Abstract: Computational fluid dynamics (CFD) is a powerful tool used to investigate the hydrodynamics in various chemical devices. As one of the typical process intensification equipment, rotating packed beds (RPBs) have been widely used in various fields. However, it is still a challenge to obtain the detailed information by CFD analysis due to the complex packing structure in the rotor of a RPB. In this study, we firstly built a three dimensional (3D) physical model with the same structure and size as the physical RPB and structured stainless steel wire mesh packing. The realizable k - ε model is applied to investigate the gas pressure drop, pressure distribution, and gas flow at different rotational speeds and gas flow rates. Based on the breakdown of the overall gas pressure drop, the gas pressure drop in the inner cavity zone is the major contributor to the overall gas pressure drop under most operation conditions. The 3D physical model describing the actual RPB can give deep understanding of the gas flow in the entire RPB as well as the gas flow behavior around every fiber of the packing. Furthermore, one special phenomenon of strong turbulence, named as gas-side end effect, was revealed in the outer annular packing zone in the rotor.